Harnessing type I interferon-mediated immunity to target malignant brain tumors - Lim, Juhee; Kang, In; La, Jeongwoo; Ku, Keun Bon; Kang, Byeong Hoon; Kim, Yumin; Park, Won Hyung; Lee, Heung Kyu (Frontiers in Immunology, 2023)
Type I interferons have long been appreciated as a cytokine family that regulates antiviral immunity. Recently, their role in eliciting antitumor immune responses has gained increasing attention. Within the immunosuppressive tumor microenvironment (TME), interferons stimulate tumor-infiltrating lymphocytes to promote immune clearance and essentially reshape a “cold” TME into an immune-activating “hot” TME. In this review, we focus on gliomas, with an emphasis on malignant glioblastoma, as these brain tumors possess a highly invasive and heterogenous brain TME. We address how type I interferons regulate antitumor immune responses against malignant gliomas and reshape the overall immune landscape of the brain TME. Furthermore, we discuss how these findings can translate into future immunotherapies targeting brain tumors in general.